Evaluation of cattle farmers' knowledge, attitudes, and practices regarding antimicrobial use and antimicrobial resistance in Rwanda. - Elise M Hirwa; Gisele Mujawamariya; Natnael Shimelash; Anselme Shyaka (PLoS ONE, 2024)
The misuse of antimicrobials in livestock may lead to the emergence and spread of resistant pathogens harmful to human, animal, and environmental health. Therefore, determining the behavior and practices of farmers regarding antimicrobial use (AMU) and antimicrobial resistance (AMR) is crucial for addressing the growing threat of AMR. This cross-sectional study was conducted in the Eastern Province of Rwanda on 441 participants using a structured questionnaire to determine the knowledge, attitudes, and practices (KAP) towards AMU and AMR. Frequency distributions, chi-square test of association and logistic regression model were used to analyze the data. This study showed poor biosecurity measures at the farm level with various antimicrobials used here; 83.9% of participants obtained them from friends and neighbors and 61.9% used them for growth promotion. Our assessment revealed a low level of KAP towards AMR among cattle farmers from the study districts. Our data showed that at a 69% cutoff, only 52.6% of farmers had correct knowledge, whereas 56% had good attitudes (47% cutoff). Finally, 52.8% had correct practices toward AMR based on a calculated cutoff of 50%. Positive attitudes, correct knowledge, and practices regarding AMU and AMR were associated with higher educational levels. Sex was correlated with knowledge and attitudes, whereas farm location was associated with attitudes and practices. Farmers expressed a need for more access to veterinary services and AMR-related training for themselves, the community animal health workers, and veterinarians. This study highlighted the low levels of KAP associated with using antimicrobials, which may lead to the misuse of antimicrobials and the spread of AMR. It is imperative to develop and implement cross-cutting measures to minimize antibiotic usage and reduce the risk of antibiotic resistance.